2021
DOI: 10.1016/j.bbih.2021.100261
|View full text |Cite
|
Sign up to set email alerts
|

Young adults’ preferences for influenza vaccination campaign messages: Implications for COVID-19 vaccine intervention design and development

Abstract: Background Health campaign interventions, particularly those tailored to the target audience’s needs and preferences, can cost-effectively change people’s attitudes and behaviors towards better health decision-making. However, there is limited research on how to best tailor seasonal influenza vaccination campaigns for young adults. Vaccination is vital in protecting young adults and their social circles (vulnerable populations like older adults) from the influenza virus and critical in shaping the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 62 publications
(58 reference statements)
1
11
0
Order By: Relevance
“…In other words, researchers should invite women in their design and development of the interventions that are targeted to this population. In light of the constraints posed by the pandemic, such as limitations on in-person meetings [ 54 ], another way to adopt the co-design method in developing women-specific physical activity interventions is via developing a theory-guided and evidence-based campaign and then gaining the key target audience’s insights [ 55 ], such as the example campaign the authors developed in the current study (see Figure 2 ). A schematic representation of the proposed co-design model could be found in Figure 3 .…”
Section: Discussionmentioning
confidence: 99%
“…In other words, researchers should invite women in their design and development of the interventions that are targeted to this population. In light of the constraints posed by the pandemic, such as limitations on in-person meetings [ 54 ], another way to adopt the co-design method in developing women-specific physical activity interventions is via developing a theory-guided and evidence-based campaign and then gaining the key target audience’s insights [ 55 ], such as the example campaign the authors developed in the current study (see Figure 2 ). A schematic representation of the proposed co-design model could be found in Figure 3 .…”
Section: Discussionmentioning
confidence: 99%
“…To successfully and effectively protect nursing home residents from global health crises such as COVID-19, stakeholders such as policy-makers, healthcare professionals, researchers informal caregivers and older adults themselves all need to contribute to the changemaking process (eg, research safeguards or underscores the importance of COVID-19 protective measures). [44][45][46][47][48][49] While some effective changes are resource intensive, time consuming and need concerted efforts from multilevel stakeholders to achieve, there are cost-effective, efficient and accessible health solutions available to nursing home residents, such as technology-based interventions. 50 51 Technology-based interventions can be considered as the use of technology (eg, digital devices such as tablets and wearable devices, communication platforms) to manage or support health promotion strategies that could offer accessible, affordable, convenient, and user-friendly health solutions to a target audience.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…The above areas of inquiry resonate with the core principles of the socioecological model,40–43 which highlights the way individuals are influenced by a series of synergistic interactions between intrapersonal and interpersonal factors (eg, residents, resident families), organisational characteristics (eg, nursing homes), policy (eg, legislative response) and the social/community (eg, ageism) context and how these processes can change over time (see figure 1.) To successfully and effectively protect nursing home residents from global health crises such as COVID-19, stakeholders such as policy-makers, healthcare professionals, researchers informal caregivers and older adults themselves all need to contribute to the change-making process (eg, research safeguards or underscores the importance of COVID-19 protective measures) 44–49. While some effective changes are resource intensive, time consuming and need concerted efforts from multilevel stakeholders to achieve, there are cost-effective, efficient and accessible health solutions available to nursing home residents, such as technology-based interventions 50 51…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kim et al (2020) found that the presence of fear appeals was associated with greater motivation to process human papillomavirus (HPV) protection-related information. While some other research studies demonstrated that individuals self-reported a higher level of discomfort, less attention, and lower level of self-efficacy when seeing fear appeals in vaccine promotion messages ( Ort and Fahr, 2018 ; Su et al, 2021 ). Thus, it is still unclear how fear appeals in vaccine campaign messages (e.g., the presence of negative pictures and content) affects motivations to control the danger or threat.…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies have yielded mixed findings regarding the effect of fear appeals (e.g., So, 2013 ; Carcioppolo et al, 2017 ; Ort and Fahr, 2018 ; Kim et al, 2020 ; Su et al, 2021 ). For example, Kim et al (2020) found that the presence of fear appeals was associated with greater motivation to process human papillomavirus (HPV) protection-related information.…”
Section: Introductionmentioning
confidence: 99%